SPE Europec Featured at 80th EAGE Conference and Exhibition 2018
DOI: 10.2118/190861-ms
|View full text |Cite
|
Sign up to set email alerts
|

NanoSurfactant: A Novel Nanoparticle-Based EOR Approach

Abstract: This paper describes a nanoparticle-based approach for stabilizing the low-cost petroleum sulfonate surfactants in high salinity and temperature water to enable their utility in EOR applications in typical carbonate reservoirs. The paper presents and discusses experimental results on the phase behavior of three of such NanoSurfactant formulations and their interfacial tensions (IFT) with crude oil, in order to evaluate their ability to mobilize oil during EOR operations. The three NanoSurfactant formulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…We first investigated the colloidal stability of Pure Sulf and Sulf+Coca formulations in deionized water and high salinity water (see the Experimental Section in Materials and Methods for the notations of the formulations). As has been identified, Pure Sulf solutions were unstable in high salinity water and precipitated immediately after preparation. Figure shows the DLS measurements of Pure Sulf oil-swollen micelles in deionized water, Sulf+Coca oil-swollen micelles in deionized water, and Sulf+Coca oil-swollen micelles in high salinity water. As shown, Pure Sulf solution has the highest polydispersity with their measured hydrodynamic diameters ranged from 10 to 400 nm.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…We first investigated the colloidal stability of Pure Sulf and Sulf+Coca formulations in deionized water and high salinity water (see the Experimental Section in Materials and Methods for the notations of the formulations). As has been identified, Pure Sulf solutions were unstable in high salinity water and precipitated immediately after preparation. Figure shows the DLS measurements of Pure Sulf oil-swollen micelles in deionized water, Sulf+Coca oil-swollen micelles in deionized water, and Sulf+Coca oil-swollen micelles in high salinity water. As shown, Pure Sulf solution has the highest polydispersity with their measured hydrodynamic diameters ranged from 10 to 400 nm.…”
Section: Resultsmentioning
confidence: 88%
“…Two surfactant formulations were prepared: (i) “Pure Sulf” oil-swollen micelles with 0.1 wt % chemicals (95 wt % Sulf and 5 wt % Deca within the chemicals) and (ii) “Sulf+Coca” oil-swollen micelles with 0.2 wt % chemicals (43.2 wt % Sulf, 54.5 wt % Coca, and 2.3 wt % Deca within the chemicals). The particular compositions were chosen based on prior studies optimized for enhanced oil recovery operations. Both formulations were prepared in deionized water or high salinity water for consecutive characterization experiments. Note for the formulations in high salinity water surfactants were first mixed in deionized water at higher concentration and then the high salinity water was added to reach the desired concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions of 0.2 wt% EOR surfactant, labeled as Sample A and Sample B, were prepared. Sample A was a mixture of alkylbenzene sulfonate and cocamidopropyl hydroxysultaine as described previously 44,45 . Sample B is a commercially available surfactant, cocamidopropyl hydroxysultaine (Petrostep -SB, 43 wt% active, Stepan Company, Northfield, IL) and was prepared by diluting the stock solution with seawater to achieve 0.2 wt%.…”
Section: Experiments and Methodologymentioning
confidence: 99%
“…The entry of engineering into the nanoscale has opened up many new areas previously inaccessible without the use of nanotechnology, as well as the possibility of modifying existing technological solutions (e.g., EOR processes). Examples of research projects or nanotechnology-based solutions have been cited repeatedly [8,14,16,[20][21][22][23][24][25][26]. These studies have shown that during EOR processes, rock wettability is particularly important in carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%